Analisis Tingkat Akurasi Penetapan Nilai Jual Objek Pajak Bumi dengan Harga Pasar Tanah Menggunakan Metode Assessment Sales Ratio: Studi Empiris di Kecamatan Cisaat Kabupaten Sukabumi - Jodhistira Sarwa Adhigana; Usman Sastradipraja (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the level of accuracy, uniformity, and the tendency toward regressivity or progressivity in the determination of Land Tax Object Sales Value (Nilai Jual Objek Pajak/NJOP) compared to land market values in Cisaat District, Sukabumi Regency. The research employs a descriptive qualitative approach using the Assessment Sales Ratio (ASR) method as an analytical tool to evaluate the conformity between NJOP and land market prices. The data were obtained from 33 land sale transactions conducted in 2024, which were selected based on applicable regulatory criteria. The results indicate that most land NJOP values in Cisaat District remain below market values, resulting in a relatively low level of accuracy that does not meet the standards recommended by the Directorate General of Taxes and the International Association of Assessing Officers (IAAO). Furthermore, the uniformity of NJOP determination across regions is found to be low, as reflected by significant disparities in ASR values. The study also reveals a regressive tendency in NJOP determination, where properties with lower market values are subject to higher effective tax burdens compared to higher-value properties. These findings highlight the need for periodic reappraisal and systematic updating of the NJOP database to enhance tax equity and optimize local revenue from Rural and Urban Land and Building Tax (PBB-P2).